Tantangan Kebijakan Otonomi Daerah di Indonesia dalam Perspektif Komunalisme di India - As Martadani Noor (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2002)
The act of Region autonomy has implemented by Indonesian government since four years ago, which is purpose to give authorities more large for doing self regulation and self determination of local government as well as local society. All those have to be done by principles of democratization, social participation, even distribution, justice, local potential, and region pluralist. Following policies of region autonomy implementation in Indonesia is colored by social conflict of ethnic and religion for long time. The emergence ethnocentrism, movement of local elite and institutionalism of religion, in which all those can encourage communalism movement. In the other word that policies of region autonomy should be can a trigger communalism movement. In the context discuss of communalism movement, which is India has experience regarding to communalism movement that is influence Indians' democratization. This article is to discuss how far the communalism pluralist is influential in realities of politic in India? What kind of learning realities of political in India? And what is challenging of region autonomy policy related with potential of Indonesian communalism? A learning of communalism pluralist and its influential in realities of politic in India, at least there is five challenge ofregion autonomy policy related with potential of Indonesian communalism namely: (1) To avoid a trigger ofsocial economic imbalance between communal, the government should be making a regulation ofsocial economic for any communal to protect "market intervention", which can be damaging economic communal. Beside, should be there a government facilities special for any economic communal that can be solving its weakness any aspect. (2) To make a regulation for conducting "cross cultural membership" on local government, industrial, social organization (non religion) and for conducting a "multiparty system" as well as "multidimensional party system " on politic parties especially. (3) A regulation of local language that purpose limited to become as formal language and to avoid local language as instrument political vested interest of self communal, which is neglecting the Indonesian language. (4) An act social conflict - special provisions regarding to conflict of ethnic and religion -, that can be giving sanction at a level of threatening nation integrity. (5)An act of Worship Placefor regulating its building.